The Antecedent of Intention to Visit Halal Tourism Areas using the Theory of Planned Behavior: The Moderating Effect of Religiosity - Julina; Asnawi, Aisah; Sihombing, Pardomuan Robinson (Journal of Tourism Management Research, 2021)
Halal tourism has a significant current market share. The increasing number of tourists from Muslim countries is a consideration for many areas to change their marketing strategies. In various works of literature, religiosity plays a role in consumer behavior. In this study, religiosity becomes a mediating variable from the subjective norm, attitude, and perceived behavioral control (PBC) to the intention to visit a halal tourism area. This study modifies the Theory of Planned Behavior (TPB), intending to understand how intense religiosity affects tourists’ decisions to visit a halal tourism area. The number of respondents in this study amounted to 590 people. Questionnaires were distributed via Google forms to tourists in Indonesia and analyzed through Moderated Regression Analysis to test the moderating effect of the religiosity variable. This research shows new information related to the religiosity variable. TPB can predict the intention to visit a halal tourism area. Subjective norms and attitudes have a positive and significant impact, while PBC has a positive but insignificant impact on intention. Still, religiosity does not play a role in strengthening the three exogenous variables that can affect the intention to visit a halal tourism area. The insignificant impact of religiosity in moderating the three independent variables may be because, in Muslim-majority countries, domestic tourists do not have to consider the halal aspect of a halal tourism area. Halal restaurants and places of worship are relatively easy to find, especially in provinces that are known for having a religious presence.